2005
DOI: 10.1021/la0511687
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical Sensing of DNA Sequences Using Piezoresistive Cantilevers

Abstract: A microfabricated cantilever with an internal piezoresistive component has been sensitized with thiol tethered ss-DNA strands and utilized for an in situ, label-free, highly specific, and rapid DNA detection assay. The generation of a differential surface stress onto the functionalized cantilever surface upon target recognition has allowed nanomechanical identification of 12-nucleotide complementary DNA probes with single base mismatch discrimination (sensitivity of 0.2 microM). Interestingly, utilization of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
110
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 19 publications
1
110
0
Order By: Relevance
“…In static mode of operation, cantilever end point deflection due to the target-receptor interactions induced differential stress on the opposite faces of the cantilever is measured. Typical applications of static mode operated piezoresistive nano cantilever platform biosensors include detection of cancer tissues, 10 viruses, 11 cardiac disease markers 12 and DNA sequencing 13 to mention a few. Even though, piezoresistive nano cantilever sensors have numerous advantages, they suffer from a major limitation in the form of thermal drift in their output characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In static mode of operation, cantilever end point deflection due to the target-receptor interactions induced differential stress on the opposite faces of the cantilever is measured. Typical applications of static mode operated piezoresistive nano cantilever platform biosensors include detection of cancer tissues, 10 viruses, 11 cardiac disease markers 12 and DNA sequencing 13 to mention a few. Even though, piezoresistive nano cantilever sensors have numerous advantages, they suffer from a major limitation in the form of thermal drift in their output characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, techniques derived from atomic force microscopy have attracted growing interest in the last 10 years. Microcantilevers were used as effective tools for a wide range of sensing applications in chemistry and life sciences and a number of reports exist on very sensitive cantilever-based assays for a multitude of analytes such as DNA (Fritz, 2000;Hansen et al, 2001;McKendry et al, 2002;Mukhopadhyay et al, 2005;Su et al, 2003;Zhang et al, 2006;Ndieyira et al, 2008), antigens, proteins, bacteria, pathogens (Arntz et al, 2003;Campbell et al, 2007;Gupta et al, 2004;Lee et al, 2005;Maraldo and Mutharasan, 2007;Wee et al, 2005), and ions (Ji and Thundat, 2002;Ji et al, 2000). Moreover, artificial noses (Baller et al, 2000), sensors for temperature change (Huang et al, 2008;Barnes et al, 1994;Berger et al, 1996), for infrared detection (Huang et al, 2008;Ivanova et al, 2005) and identification of explosives (Gilda et al, 2011;Pinnaduwage et al, 2003a,b;van Neste et al, 2008) were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the stimulus is an external force/deflection applied to the cantilever or a surface stress which is induced by the analyte-receptor type binding reactions on the cantilever surface. Some examples of force type are atomic force microscopy, 1-6 force sensor, 7-9 flow sensor [10][11][12] whereas, those of surface stress type are chemical/biochemical sensor, [13][14][15] biosensor, 16,17 DNA sequencing 18 and environment sensor. 19 The present study will focus on the piezoresistive microcantilevers that are used in surface stress studies.…”
Section: Introductionmentioning
confidence: 99%